Efeitos da reabilitação cardiovascular em crianças com cardiopatia congênita - Navarro, Flavia Cristina (2020)
Home physical training is a promising alternative to conventional supervised training for patients with congenital heart disease ( Although the beneficial effects of exercise interventions is well established in patients with CHD, there is still a lac k of knowledge about the variety and usefulness of existing programs. Therefore, the aim of this study was to conduct a systematic review and meta analysis of randomized controlled trials publications on the population of children with CHD, which analyzes outpatient and home cardiopulmonary rehabilitation in children with congenital heart disease. The searches were carried out in the MEDLINE and PEDro databases. The PICO search strategy was adopted: P ( Child with CHD; I ( Outpatien t rehabilitation and home rehabilitation; C ( no activity; O ( peak VO2. Six studies were included in the narrative analysis and all were published in English. RCTs were performed in Canada (n 2), France (n 2), Norway (n 1) and Hol land (n 1). The total number of participants analyzed in all studies was 321 participants (conventional rehabilitation 81 and 63 control; home rehabilitation 98 and 79 control). Regarding gender discrimination, 150 boys and 171 girls were reported. The a ge range of participants was 6 to 15 years, with most studies reporting mean ages ≤ A total of six studies involving 578 participants were included. The three studies reporting the peak VO2 at the beginning and after training, which included 144 patient s (Rehabilitation 81 patients Control 63 patients). This comparison was statistically significant 2.81 [ 4.74]; Z 2.86 (p < and I2 49%. The other three studies reported peak VO2 at baseline and after home rehabilitation, including 177 pati ents (Reab 98 patients Control 70 patients). This comparison, however, was not statistically significant (p 0.66). The present data suggest that outpatient rehabilitation in children is more effective than home rehabilitation when oxygen consumption an alises is considered.